2010
DOI: 10.3390/ijerph7052208
|View full text |Cite
|
Sign up to set email alerts
|

Publically Funded Recreation Facilities: Obesogenic Environments for Children and Families?

Abstract: Increasing healthy food options in public venues, including recreational facilities, is a health priority. The purpose of this study was to describe the public recreation food environment in British Columbia, Canada using a sequential explanatory mixed methods design. Facility audits assessed policy, programs, vending, concessions, fundraising, staff meetings and events. Focus groups addressed context and issues related to action. Eighty-eighty percent of facilities had no policy governing food sold or provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 19 publications
7
61
0
Order By: Relevance
“…Establishing policies regarding foods available at sporting events is a promising public health step, because it appears few have established policies. 31 Because 52% of outdoor sports facilities are community owned and operated, 4 engaging parents and sports leagues to conduct family-based interventions may be feasible ways to improve activity and nutrition behaviors at the community level.…”
Section: Resultsmentioning
confidence: 99%
“…Establishing policies regarding foods available at sporting events is a promising public health step, because it appears few have established policies. 31 Because 52% of outdoor sports facilities are community owned and operated, 4 engaging parents and sports leagues to conduct family-based interventions may be feasible ways to improve activity and nutrition behaviors at the community level.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] However, despite their health mandate, 8,9 many have unhealthy food environments that may paradoxically increase children's obesity risk. [10][11][12][13][14][15][16] Some recreation stakeholders are willing to improve the quality of their food environments; however, barriers, including the provisions of foodservice contracts, fears of reduced profitability, and lack of resources and knowledge, limit their opportunities for change. 11,12,15,17 To improve the quality of community food environments, the provincial government of British Columbia (BC), Canada, developed nutrition guidelines for food sales in public buildings, including recreation and sports facilities.…”
Section: Introductionmentioning
confidence: 99%
“…A survey and needs assessment conducted in British Columbia (BC) in 2006, confirmed that these food environments did not enable healthy choices for families and children but that recreation stakeholders were interested in change [13]. Shortly afterwards, the Nutrition Guidelines for Vending Machines in BC Public Buildings were developed to help govern food and beverages sold in local government buildings, including recreation and sport facilities [14].…”
Section: Introductionmentioning
confidence: 99%